2022
DOI: 10.3389/fvets.2022.877066
|View full text |Cite
|
Sign up to set email alerts
|

Trans-anethole Ameliorates Intestinal Injury Through Activation of Nrf2 Signaling Pathway in Subclinical Necrotic Enteritis-Induced Broilers

Abstract: This study was conducted to investigate the alleviative effects of trans-anethole (TA) on intestinal oxidative stress by enhancing the activities of intestinal antioxidant enzymes and activating the Nrf2 signaling pathway in subclinical necrotic enteritis (NE) infected broilers. A total of 192 1-day-old male Arbor Acres broilers were randomly allocated into three treatment groups: (1) control (CON); (2) subclinical NE challenge (NE); (3) NE challenge + 600 mg/kg TA (NE+TA600). Subclinical NE was induced by ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…These results demonstrate that the combined infection of coccidia and C. perfringens caused oxidative stress. This is basically consistent with previous studies [ 7 ]. We observed that dietary supplementation with 12,000 IU/kg VA failed to alleviate the oxidative stress of NE-infected broilers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results demonstrate that the combined infection of coccidia and C. perfringens caused oxidative stress. This is basically consistent with previous studies [ 7 ]. We observed that dietary supplementation with 12,000 IU/kg VA failed to alleviate the oxidative stress of NE-infected broilers.…”
Section: Discussionsupporting
confidence: 94%
“…A healthy intestine is a material mechanism for the high production of poultry [ 5 ]; while oxidative stress and inflammatory responses cause intestinal damage in poultry, an injured intestine opens the door for pathogenic microorganisms and stimulators, which will have negative effects on the growth performance and health of poultry [ 6 ]. Coccidia and C. perfringens are the main accomplices in necrotic enteritis (NE) in poultry, and NE causes the abnormal expression of antioxidant enzymes and peroxide products [ 7 ]. In addition, intestinal barrier-related proteins such as tight-junction proteins might be overexpressed in response to inflammation [ 8 , 9 ], and an excessive inflammatory response downregulates their expression and destroys the intestinal barrier [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Necrotic enteritis (NE) is a prevalent infectious gastrointestinal illness in broiler production, predominantly caused by Clostridium perfringen . C. perfringens is secondary to coccidia (coccidia is primary), or they may be co-infected, resulting in an inflammatory reaction of the intestinal mucosa and oxidative stress, which can cause a tremendous economic loss in the poultry industry [ 1 , 2 , 3 , 4 ]. Oxidative stress and inflammation disrupt mucosal cells and tight junction proteins, impeding the self-repair mechanisms of the intestinal barrier [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%